Evaluasi Kinerja Halte Bus Dengan Metode Servqual (Studi Kasus Halte Trans Jogja Trayek 1A, 1B, 2A, Dan 2B) - Nur Baskoro Adi; Sigit Priyanto; Siti Malkhamah (TEKNISIA, 2020)
In 2008, the city of Yogyakarta adopted a buy the service scheme in the Trans Jogja public transport aiming to improve the quality of public transport and reduce congestion. Based on the study of GIZ-SUTIP in 2012, there were several problems in Trans Jogja, including inadequate bus stops and excessive staff numbers. The aim of our study were to evaluate and improve bus stops performance and analyze bus stop service quality according to passenger perceptions. This study is a descriptive study using purposive sampling technique, conducted on 12 Trans Jogja bus stops and 180 respondents. The data obtained were analyzed using MS Excel and SPSS 22 computer program. The results showed that bus stop performance was not good on headways, waiting times, and on-time performance. The clearance time of far-side bus stops was shorten than near-side and mid block bus stops. The near-side and far-side bus stops were accessed by passengers on foot. The service quality of the Trans Jogja shelter does not match the expectations of the passengers with a Gap Servqual value of -0.790. The service attribute was in quadrant C of the Cartesian Diagram, that requires corrective action from the Trans Jogja operator.